Transanal Endoscopic Proctectomy: a new approach to the total excision of the mesorectum - Mendes,Carlos Ramon Silveira (2015)
ABSTRACTIntroduction:Colorectal cancer is a serious public health problem. In 1982, Heald managed to reduce mortality by standardizing the total excision of mesorectum. The use of transanal endoscopic microsurgery has emerged to allow resection of rectal tumors as a minimally invasive method. With the association of Transanal Endoscopic Operation with total excision of mesorectum, it was possible to develop a new approach for total excision of mesorectum.Surgical technique:The procedure is started by the perineal time with Transanal Endoscopic Operation device; introduction of Transanal Endoscopic Operation system follows, with exposure of the lesion with a circumferential incision at a distance between 2 and 4 cm from distal tumor margin after making a purse string suture to close the rectal stump. Then, dissection is carried out by the posterior portion until reaching the presacral avascular fascia, completing the mesorectal circumferential dissection until the peritoneal reﬂection. After this step, a laparoscopic procedure is performed with the use of three trocars, with mobilization of splenic ﬂexure and ligation of the inferior mesenteric artery, as well as confection of a protective ileostomy. Then, transanal removal of the surgical specimen is performed, and the procedure goes on with a coloanal anastomosis.